Green Nanotechnology a review in last 5 years for AuNPs - Williams De Jesús Jiménez Martínez; Juan Carlos Vázquez Lira (Mundo Nano)
Green chemistry, based on the principles of Paul Anastas and John Warner, promotes the sustainable synthesis of gold nanoparticles (AuNPs) by reducing the use of toxic substances and minimizing hazardous waste. Traditional methods, which employ reducing agents such as sodium borohydride (NaBH4), generate harmful by-products, while green approaches use natural agents such as plant extracts and microorganisms that act as reductants and stabilizers, without generating toxic waste. These methods are not only safer, but also improve the biocompatibility of AuNPs, making them much more suitable for biomedical applications, notably drug delivery, targeted therapies and molecular diagnostics. The use of natural sources and biocatalysts, such as enzymes or microorganisms, facilitates synthesis under mild conditions, allowing greater control over the shape and size of AuNPs. These nanoparticles can be designed to specifically target cells, improving the efficacy of cancer treatments and reducing adverse effects. In this article we present the main features and advantages of green synthesis of AuNPs for a promising alternative with significant applications in nanomedicine and other technological areas.